Synthesis, characterization and biological screening of N-heterocyclic carbene Ag(I) catalysts for aldehyde–amine–alkyne coupling reaction : Bioligical potential of benzimidazole-2-ylidene silver complexes - Boubakri, Lamia; Mnasri, Aziza; Ben Salah, Donia; Mansour, Lamjed; Gürbüz, Nevin; Özdemir, İsmail and Sauthier, Mathieu and Hamdi, Naceur (Cellular and Molecular Biology, 2025)
N-heterocyclic carbenes (NHCs) are widely recognized for their applications in organometallic chemistry, catalysis, and pharmaceutical research due to their unique steric and electronic properties. In this study, we report the synthesis of six novel unsymmetrical N,N-disubstituted benzimidazolium salts (2a–f) and their corresponding silver-NHC complexes (3a–f). The structures of all compounds were characterized using nuclear magnetic resonance (NMR), Fourier-transform infrared spectroscopy (FT-IR), and elemental analysis. The biological potential of these compounds was evaluated through in vitro antimicrobial assays against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans, and Candida glabrata. Additionally, anticancer activity was tested against A549, HCT116, and BEAS-2B cell lines, revealing promising results for some derivatives. Preliminary catalytic studies demonstrated the effectiveness of the silver-NHC complexes in A3-coupling reactions involving aldehydes, alkynes, and amines. These reactions yielded propargylamines with high conversion rates (up to 90%) using minimal catalyst amounts. This work highlights the dual utility of these compounds as both potent biological agents and efficient catalysts, paving the way for further exploration of their applications in medicinal chemistry and sustainable catalysis.